Potential global fire monitoring from EOS-MODIS - Kaufman, Yoram J.; Justice, Christopher O.; Flynn, Luke P.; Kendall, Jackie D.; Prins, Elaine M.; Giglio, Louis; Ward, Darold E.; Menzel, W. Paul; Setzer, Alberto W. (Journal of Geophysical Research, Washington, DC, 1998)
The National Aeronautic and Space Administration (NASA) plans to launch the moderate resolution imaging spectroradiometer (MODIS) on the polarorbiting Earth Observation System (EOS) providing morning and evening global observations in 1999 and afternoon and night observations in 2000. These four MODIS daily fire observations will advance global fire monitoring with special 1 km resolution fire channels at 4 and 11 μm, with high saturation of about 450 and 400 K, respectively. MODIS data will also be used to monitor burn scars, vegetation type and condition, smoke aerosols, water vapor, and clouds for overall monitoring of the fire process and its effects on ecosystems, the atmosphere, and the climate. The MODIS fire science team is preparing algorithms that use the thermal signature to separate the fire signal from the background signal. A database of active fire products will be generated and archived at a 1 km resolution and summarized on a grid of 10 km and 0.5°, daily, 8 days, and monthly. It includes the fire occurrence and location, the rate of emission of thermal energy from the fire, and a rough estimate of the smoldering/flaming ratio. This information will be used in monitoring the spatial and temporal distribution of fires in different ecosystems, detecting changes in fire distribution and identifying new fire frontiers, wildfires, and changes in the frequency of the fires or their relative strength. We plan to combine the MODIS fire measurements with a detailed diurnal cycle of the fires from geostationary satellites. Sensitivity studies and analyses of aircraft and satellite data from the Yellowstone wildfire of 1988 and prescribed fires in the Smoke, Clouds, and Radiation (SCAR) aircraft field experiments are used to evaluate and validate the fire algorithms and to establish the relationship between the fire thermal properties, the rate of biomass consumption, and the emissions of aerosol and trace gases from fires.